Environmental stability increases relative individual specialisation across populations of an aquatic top predator. Issue 2 (29th September 2017) - Dermond, Philip; Thomas, Stephen M.; Brodersen, Jakob
Abstract : The concept of the niche has long been a central pillar in ecological theory, with a traditional focus on quantifying niches at the species or population level. However, the importance of individual‐level niche variation is increasingly being recognised, with a strong focus on individual specialisation. While examples illustrating the contribution of the individual niche to whole population niche structure are accumulating rapidly, surprisingly little is known about the conditions that shape the differences between these two potentially divergent components. Though theory predicts that stability should influence the extent of such intra‐specific specialisation, we know of no previous study that has investigated its role in individual specialisation, and the differentiation between individual‐ and population niches. Here, we studied the diet of individuals from multiple populations of an aquatic top‐predator, Salmo trutta, inhabiting contrasting stable, groundwater fed and unstable, surface water fed pre‐alpine streams. Based on stomach content analysis, we found that individuals living in stable environments displayed a higher degree of specialisation than those in unstable environments, with the between‐individual component of niche width being approximately twice as high in the former. We subsequently validated these results by evidence gained from stable isotope analysis of muscle tissue. As such, we reveal that environmental stability can significantly influence individual niches within populations, leading to increased specialisation.